Simulation design for improvement of undergraduate nursing students' experience of evidence-based practice: A scoping-review protocol. - Chi Eun Song; Aeri Jang (PLoS ONE)
Simulation may be an effective educational strategy for undergraduate nursing students to experience evidence-based practice. The aim of this scoping review is to explore such simulations to discover the design characteristics that best achieve this goal. In this review, we will consider studies in which the focus was on evidence-based practice-related simulation programs for undergraduate students in academic, clinical, or virtual settings. We will also focus on the active learning strategies applied in such simulation programs. This scoping review will be conducted in accordance with the Joanna Briggs Institute methodology. Studies will be searched in Medical Literature Analysis and Retrieval System Online (MEDLINE; PubMed), the Cumulative Index to Nursing and Allied Health Literature (CINAHL), the Education Resources Information Center (ERIC), and the Excerpta Medica database (EMBASE). Sources of unpublished studies/gray literature will not be included in this scoping review. Data extraction will be undertaken by using a data-extraction tool developed by the reviewers, based on the National League for Nursing Jeffries Simulation Theory. Via a narrative summary and tabulated results, we will describe how the simulation programs were designed or implemented in an undergraduate curriculum.